The genus Lepidozetes Berlese, 1910 (Acari: Oribatida: Tegoribatidae) in Europe with description of a new species - Weigmann, Gerd (Zootaxa, 2013)
The type species of the genus Lepidozetes singularis Berlese, 1910, is redescribed, using fresh material from Italy, Switzerland and Germany. Mounted specimens from museums were compared: microscope slides of the type series of Berlese (deposited in Florence) and of the Willmann-collection (deposited in Munich). The controversial question of the validity of Lepidozetes conjunctus Schweizer, 1922, is reconsidered using the single original material from Schweizer, a microscope slide with the type specimen. This study confirms that L. conjunctus should be considered a junior synonym of L. singularis. A new species of the genus, Lepidozetes bavaricus n. sp., is described. This second European species was collected in Southern Germany (Altmühltal, Bavaria) in a valley slope with extreme sun-exposure.